Do external environmental factors affect on strategic choice decisions of innovation?: The case of service organizations in a cross-cultural comparison. Issue 3 (3rd July 2019) - Aikaterini, Galanou N.; Ioannis, Sotiropoulos; Vasilagos, Tryfon
Abstract: Decision making of innovation comes to the fore as sufficient justification for achieving competitiveness in a context of ever-increasing rivalry. In this formulation, decision makers are likely to form mental frames and sense-making processes in order to access complex interactions of external and organizational ingredients and make strategic decisions of innovation alternatives (service innovation, process innovation, ancillary innovation). This paper examines environmental factors that may explain managers' strategic choice of a specific type of innovation in service sector organizations located in Qatar and Greece from the viewpoint of the managers' distinct national cultures resulting in different attitudes and values. This research work examines several main-effect propositions regarding managers' perspective chosen innovation alternatives, depending on the external forces (service need, diversity of need, increase in population, and influence of context) are dealing with. We illustrate the main effect by looking at surface manifestations of managerial decisions of innovation as outward expressions of distinct characteristics lying deeper in each national culture of origin: Qatari managers prefer service innovations more than Greek managers do. Furthermore, this article reports on the findings of an exploratory study comparing national differences in innovation selection decision between Qatari and Greek top managers that develop a number of interaction effects. To confirm our propositions we gathered experimental data from 118 Greek top managers and 61 Qatari top managers. A multilevel regression analysis was used to examine and assess the relative impacts of the environmental forces on innovation strategic decision-making.